Import Competition and Public Attitudes Towards Trade - Alex Davenport; David Dorn; Peter Levell (Institute of Labor Economics (IZA), 2021)
We use data from the Pew Global Attitudes Survey to analyse how public attitudes towards trade have changed over time in developed economies, and how these attitudes differ across groups in the population. Attitudes towards trade deteriorated in the 2000s before the onset of the financial crisis, with declines tending to be greater in countries that also saw larger increases in Chinese import competition. Perhaps surprisingly, given that barriers to trade appear to be on the increase again after several decades of steady decline, attitudes towards trade improved again during the last decade both in the US and in leading European economies. Comparing across survey respondents with different individual characteristics, those without a university education are less likely to have a favourable impression of international trade, and to believe that it has specific benefits in terms of reducing prices, creating jobs, or increasing wages. While economists often emphasize the consumer benefits of trade due to lower prices, only 20-40% of survey respondents in most countries perceive such a price effect, suggesting that the benefits of trade may not be salient for many people.
Keywords: F10; F16; F60; 330; trade; attitudes; prices